Determinants of Pro Competition Functioning of Agromarkets in Tanzania: Case of Green Tea Leaves - Mlulla Allan; Deus, Ngaruko (IJRDO - Journal of Business Management, 2021)
The study investigated the factors affecting pro competition functioning of the identified relevant markets. A GLS multiple regression model was used to identify factors influencing farmers’ GM from relevant markets. Results reveal that there is need for economic regulation and that the current legal provisions are inadequate to provide for pro competition markets. The identified relevant markets are the buying and selling of green tea leaves in Southern Tanzania. Results showed that several factors do affect pro competition functioning of the three markets. It was recommended that there should be developed comprehensive legal and regulatory framework to provide for economic regulation. The identified anti-competitive issues should be pursued by the Fair Competition Commission by way of enforcement whereas non-enforcement issues should be pursued as matters of competition advocacy.